Connection between bilateral temporal regions: Tractography using human connectome data and diffusion spectrum imaging. (May 2017) - Wei, Peng-Hu; Mao, Zhi-Qi; Cong, Fei; Wang, Bo; Ling, Zhi-Pei; Liang, Shu-Li; Yu, Xin-Guang
Highlights: Temporal lobe epilepsy often propagates inter-hemispherically. DTI cannot adequately assess crossing fibers and cortical regions. We investigated the trajectory by advanced diffusion connectome technique. The splenium was further divided into 3 subregions. 3 Types of bitemporal connections were visualized and discussed. Abstract: Temporal lobe epilepsy often propagates inter-hemispherically. Although the pathway of the propagation was verified by electrophysiology, the trajectory remains poorly defined. DTI can depict fiber trajectory but it has limited angular resolution and cannot adequately assess cortical regions. We visualized potential pathways of bitemporal epilepsy propagation using diffusion spectrum imaging (DSI) with data consisting of 8 groups of 514 directions and diffusion templates of 842 subjects from the human connectome project (HCP). We verified the results with reference to the axonal-tracing literature. Both the large population overall and individual connection properties were investigated. In both the HCP 842 atlas and DSI individual data, the bilateral temporal pole was found to connect via the anterior commissure. The splenium of the corpus callosum was divided into 3 subregions (CS1, CS2, CS3) according to the form of connections. CS1 was predominately located at the rostral third and the dorsal part of middle third of the splenium; it communicated with the bilateral parietal lobe. SC2 was predominately located at the ventral middle third of the splenium. Fibers passed through the lateral wall of the lateral ventricle and connected to regions lateral of the occipitotemporal sulci. CS3 was located at the caudal third of the splenium. Together with the hippocampal commissure, its fibers constituted the medial wall of the lateral ventricle and distributed medially to the occipitotemporal sulci. The trajectory of bilateral temporal connections was visualized in this study; the results might help in the understanding and treatment of inter-hemispherical propagation of temporal-lobe epilepsy.